2016
DOI: 10.7762/cnr.2016.5.4.219
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Oral Nutritional Intervention in Malnourished Cancer Patients: a Systemic Review

Abstract: Cancer is currently a leading cause of deaths worldwide and the number of new cases is growing rapidly in both, developed and developing countries. Nutritional management during and after cancer treatment affects treatment efficacy and patient quality of life (QOL). This review systemically examined the effect of oral nutritional interventions on nutritional and clinical outcomes in cancer patients. We especially focused on outcomes such as nutritional status indices, immune-associated biochemical markers, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 87 publications
(78 reference statements)
1
18
0
2
Order By: Relevance
“…Thus, enhancing preoperative nutritional statues by early identification of nutritional status using the MUST have demonstrated good outcomes which is evidenced in our study. This is supported by several studies [1,9,13,30,33], where positive outcomes prediction associated with the use of MUST were demonstrated in terms of length of hospitalization stay, mortality, hospitalization cost and improved quality of life. In addition, it was observed that participants who were non-smokers and underwent primary surgical closure were related to decreased length of hospitalization stay.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Thus, enhancing preoperative nutritional statues by early identification of nutritional status using the MUST have demonstrated good outcomes which is evidenced in our study. This is supported by several studies [1,9,13,30,33], where positive outcomes prediction associated with the use of MUST were demonstrated in terms of length of hospitalization stay, mortality, hospitalization cost and improved quality of life. In addition, it was observed that participants who were non-smokers and underwent primary surgical closure were related to decreased length of hospitalization stay.…”
Section: Discussionsupporting
confidence: 57%
“…Postoperative complications are often challenging to manage due to preexisting poor nutritional state [9], which is a contributing factor in the spiral effects of postoperative complications and mortality particularly in patients with head and neck cancer [1,5,32]. Increased postoperative infection rates ranging from 20 to 40%, were observed in both surgical and non-surgical-related infections and were significantly correlated with patients who were malnourished at diagnosis [9,10,13,17,26,33]. Therefore, preoperative assessment of nutritional status using a validated screening tool that has high specificity and sensitivity is vital in the initial screening of patients so that accurate assessment of their nutritional status can be established.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plus spécifiquement la méta-analyse de Milne et al (2009) incluant 62 études et plus de 10 000 personnes âgées à risque de dénutrition, a montré qu'une prise de CNO HP/HC augmente de façon significative le poids de 2,2 % (Milne et al, 2009). Ces résultats positifs sont également observés chez des personnes âgées atteintes de démence (Allen et al, 2013) et une majorité d'individus atteints de cachexie cancéreuse (selon le type de cancer et de traitement) (Kim et Sung, 2016 ;Laviano et al, 2016). Une autre revue de la littérature (Cawood et al, 2012) montre que la prise en charge de la dénutrition par des CNO hyperprotidiques permet d'augmenter significativement le poids et la force musculaire de préhension, et de réduire significativement les complications (À30 %) et les réadmissions à l'hôpital (À40 %).…”
Section: Les Preuves D'efficacité Des Cnounclassified